Impacts of Climate and Land Use Changes on Projected Discharge Patterns in the Upper Yellow River Basin - Ziyan Chen; Buda Su; Nicola Fohrer; Ayenew D. Ayalew; Jinlong Huang; Mengxia Zhao; Shanshan Wen; Tong Jiang (International Journal of Climatology, 2025)
This study explores the combined impacts of climate and land use changes on the discharge of the Upper Yellow River Basin (UYR), an area of significant water conservation, employing Coupled Model Intercomparison Project Phase 6 (CMIP6) climate models and land use statistics. Discharge projections were conducted by hydrological models for the near‐term (2021–2040), mid‐term (2041–2060) and long‐term (2081–2100) under seven shared socioeconomic pathways (SSPs). The study's key findings are as follows: (1) temperature and precipitation are projected to increase under all SSPs, with greater rates under higher radiative forcing scenarios. Barren land is expected to undergo the most significant changes in land use, followed by grassland and forest, with the largest variations occurring in the long term. (2) The combined impacts of climate and land use changes lead to an overall increase in annual and seasonal discharge, with the most pronounced increases in spring. Under SSP5–8.5, spring discharge is projected to increase by up to 90.19% in the long term. Changes in discharge extremes also suggest an increasing likelihood of floods and droughts. (3) Land use changes play a crucial role in discharge estimation. Neglecting land use dynamics leads to significant overestimation of summer discharge, exceeding 4000 km 3 /y under all SSPs across different time periods. This study provides more reliable scenarios for future discharge changes in the UYR and emphasises the crucial role of land use in discharge projections.